Ratzinger, Marxism and Liberation - Eslava, Euclides (Cuestiones Teológicas, 2025)
Marxism continues to influence contemporary philosophical, political, and theological debates. In recent theology, it marked a new era with its influence on “Liberation Theologies”. Joseph Ratzinger studied it from his youth and led the works that defined the Magisterium’s new stance toward Latin American theology. This article traces his thoughts on Marxism to highlight the main conclusions at each stage of its evolution and infer the practical consequences for society and the Church. As a secondary objective, his interpretation of the intellectual itinerary of the West in the 20th century is examined.